Identification of Epithelial-Mesenchymal Transition-Related lncRNAs that Associated With the Prognosis and Immune Microenvironment in Colorectal Cancer - Liu, Chuan; Hu, Chuan; Li, Jianyi; Jiang, Liqing; Zhao, Chengliang (Frontiers in Molecular Biosciences, 2021)
Background: The expression of long non-coding RNA (lncRNA) is associated with the epithelial-mesenchymal transition (EMT) in tumorigenicity, but the role of EMT-related lncRNA in colorectal cancer (CRC) remains unclear. Methods: The clinical data and gene expression profile of CRC patients were obtained from The Cancer Genome Atlas database. Differential expression analysis, Cox regression model, and Kaplan-Meier analysis were used to study the relationship between EMT-related lncRNAs and the prognosis of CRC. Functional analysis and unsupervised clustering analysis were performed to explore the influence of certain lncRNAs on CRC. Finally, Cytoscape was used to construct mRNA-lncRNA networks. Results: Two signatures incorporating four and nine EMT-related lncRNAs were constructed for predicting the overall survival (OS) and disease-free survival (DFS), respectively. Kaplan-Meier survival curves indicated that patients in the high-risk group had a poorer prognosis than those in the low-risk group. Both signatures were identified as prognostic biomarkers independent of clinical variables. The results of the functional analysis suggested that the P53 and ECM-receptor pathways affect the prognosis of CRC, and AL591178.1 is a key prognostic EMT-related lncRNA, which is negatively related to immune cells, P53 pathway, and ECM-receptor pathway. Conclusion: Four OS-related and nine DFS-related EMT-related lncRNAs were correlated with the prognosis of CRC by potentially affecting the immune microenvironment, and AL591178.1 plays a key role as a prognostic factor.